Determining cohesive parameters for modeling interfacial fracture in dissimilar-metal friction stir welded joints. (1st May 2021) - Kulkarni, Shank S.; Gupta, Varun; Ortiz, Angel; Das, Hrishikesh; Upadhyay, Piyush; Barker, Erin; Herling, Darrell
Abstract: Predicting the structural performance of a joint requires mechanical characterization of the joint interface. Use of the cohesive-zone model (CZM) is an effective approach for implementing fractures, seams, and joints in the structures. The CZM requires a cohesive constitutive law, which, in the context of a welded joint, relates the traction at the interface to the separation displacement of the two surfaces. Typical configurations for fracture testing to obtain the parameters for a cohesive law involve assumptions including large weld areas and undisturbed substrate, making those techniques unsuitable for friction stir welded joints. This paper presents an approach of experimentation combined with finite element modeling to determine the cohesive law parameters to mechanically characterize the interface obtained in friction stir welded joints.